Literatur Review: Implementasi PjBL terhadap Kreativitas dan Berpikir Tingkat Tinggi Siswa - Islawati, Islawati; Samsuddin, Yati Bt (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out and describe the implementation of the Project-Based Learning (PjBL) project-based learning model in increasing student creativity at various levels of education. The research method used is Systematic Literature Review (SLR), which is carried out through systematic steps to identify, evaluate, and synthesize relevant articles. Articles are obtained through searches on the Sinta portal, with criteria that only include articles that are accredited and published in the last five years. The search strategy involves the use of specific keywords such as "Project-Based Learning" and "student creativity," with filtering using inclusion and exclusion criteria. From the search results, 50 articles were found which were then selected gradually to produce 10 main articles relevant to the research topic. The data analysis technique is carried out through a thematic coding approach, which involves identifying the main themes of the content of the analyzed article. The results of the study show that PjBL has a significant influence on student creativity. The main findings include improvements in several aspects of student creativity, namely fluency, flexibility, originality, elaboration, and collaboration in the learning process. Based on these results, it is proven that the project-based learning model (PjBL) is effective in significantly increasing students' creativity in various educational contexts